BRANDING THE LOCAL WISDOM OF MSMES IN INDONESIA AMID THE DIGITALIZATION OF THE GLOBAL MARKET - Siti Nurul, Khaerani; Haramain, Muhammad (Moneta: Jurnal Manajemen & Keuangan Syariah, 2026)
This article analyzes the branding of local wisdom-based micro, small, and medium enterprises (MSMEs) in Indonesia within the context of global market digitalization. The present study employs a qualitative conceptual approach, utilizing a literature review method. The analysis focuses on how MSME products rooted in local culture can strengthen their competitiveness through the integration of entrepreneurial marketing, cultural branding, and digital marketing. The findings indicate that MSME transformation is not solely determined by production capacity; the ability to create value, build brand identity, manage cultural narratives, and utilize digital technology systematically is also a contributing factor. Entrepreneurial marketing provides a relevant strategic framework because it emphasizes proactiveness, opportunity orientation, innovation, customer intensity, resource leveraging, calculated risk-taking, and value creation. Local wisdom is a source of differentiation that strengthens product positioning through authenticity, cultural symbols, community stories, and social values. Digital marketing has emerged as a pivotal medium for market expansion, effective brand communication, and continuous consumer engagement. The present article posits that Indonesian MSMEs have the potential to penetrate the global market, provided they adopt a holistic approach to integration that encompasses product innovation, storytelling, cultural branding, and consistent digital strategies. The novelty of this article lies in its formulation of an integrative framework that connects local wisdom, entrepreneurial marketing, and digitalization as the basis for transforming MSME competitiveness in the global market.